2014
DOI: 10.1080/13607863.2014.899978
|View full text |Cite
|
Sign up to set email alerts
|

Positive psychology interventions in people aged 50–79 years: long-term effects of placebo-controlled online interventions on well-being and depression

Abstract: Objectives: Various positive psychology interventions have been experimentally tested, but only few studies addressed the effects of such activities in participants aged 50 and above. Method: We tested the impact of four self-administered positive psychology interventions in an online setting (i.e., gratitude visit, three good things, three funny things, and using signature strengths in a new way) on happiness and depressive symptoms in comparison with a placebo control exercise (i.e., early memories). A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
141
3
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 162 publications
(166 citation statements)
references
References 36 publications
9
141
3
13
Order By: Relevance
“…They found increases in happiness at the onemonth and three-months follow-up and an amelioration of depression at every follow-up time point (up to six-months) in comparison to the placebo control condition (writing about early memories). In a recent study Proyer, Gander, Wellenzohn, and Ruch (2014) replicated these findings in a sample of people aged 50 to 79 for depressive symptoms, but for happiness only for the six-months follow-up. Overall, the literature on humor-based PPIs is scarce, but findings are promising.…”
Section: Humor-based Interventions and Well-being In Non-clinical Samsupporting
confidence: 66%
See 1 more Smart Citation
“…They found increases in happiness at the onemonth and three-months follow-up and an amelioration of depression at every follow-up time point (up to six-months) in comparison to the placebo control condition (writing about early memories). In a recent study Proyer, Gander, Wellenzohn, and Ruch (2014) replicated these findings in a sample of people aged 50 to 79 for depressive symptoms, but for happiness only for the six-months follow-up. Overall, the literature on humor-based PPIs is scarce, but findings are promising.…”
Section: Humor-based Interventions and Well-being In Non-clinical Samsupporting
confidence: 66%
“…When comparing sample characteristics across the three studies where this intervention has been used (i.e., the present study; Gander et al, 2013;Proyer et al, 2014), the baseline levels of depression seem to differ. Obviously levels of depression were lowest in this study, because we excluded those participants above a (sensitive) threshold for depression.…”
Section: Discussionmentioning
confidence: 99%
“…It consists of 33 sets of five statements describing an individual's feelings during the past week (e.g., "My life is a bad one" through "My life is a wonderful one"). The AHI has been widely used in research; good psychometric properties and support for its validity have been reported (e.g., Gander et al, 2013;Proyer et al, 2014;Shapira & Mongrain, 2010). The alpha coefficient in this sample was .93 (pre-test).…”
Section: Instrumentsmentioning
confidence: 96%
“…However, the expectations for the sustainability of the effects are of exploratory nature only. Only few interventions are effective for a time span of up to six months (see e.g., Gander et al, 2013;Mongrain & Anselmo-Matthews, 2012;Proyer et al, 2014;Seligman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation